Prevalence and severity of long-term physical, emotional, and cognitive fatigue across 15 different cancer entities - Schmidt, Martina; Hermann, Silke; Arndt, Volker; Steindorf, Karen (Cancer medicine, 2020)
Background Fatigue prevalence and severity have been assessed in a variety of studies, yet, not in a standardized way, and predominantly in breast cancer patients. Systematic, comparative investigations across a broad range of cancer entities are lacking. Methods The FiX study systematically enrolled 2244 cancer patients across 15 entities approximately 2 years after diagnosis. Fatigue was assessed with the multidimensional EORTC QLQ-FA12 questionnaire. Physical, emotional, cognitive, and total fatigue were compared across entities and with normative values of the general population. Differences in patients' characteristics and cancer therapy between entities were taken into account using analyses of covariance models. Results Across all entities, mean physical fatigue levels were significantly higher than age- and sex-matched means of the general population for all cancer entities (all Bonferroni-Holm adjusted P < .01). For most entities also emotional and cognitive fatigue levels were significantly higher than normative values. Age- and sex-standardized physical fatigue prevalence ranged from 31.8% among prostate to 51.7% among liver cancer patients. Differences between entities could not be fully explained by sex, age, BMI, or cancer therapy. Adjusted for these factors, mean physical fatigue was higher for stomach (P = .0004), lung (P = .034), kidney (P = .0011), pancreas (P = .081), and endometrium (P = .022) compared to breast cancer patients. Adjusted means of emotional fatigue were also lowest in breast cancer patients and significantly higher in stomach (P = .0047), bladder (P = .0036), and rectal (P = .0020) cancer patients. Conclusions Physical, emotional, and cognitive fatigue is prevalent in all 15 investigated cancer entities even 2 years after diagnosis. Fatigue in breast cancer patients, the so-far most studied group, is in the lowest range among all entities, suggesting that the extent of fatigue is still insufficiently determined. Entity-specific problems might need to be considered in the treatment of fatigue.